Mendelian randomization analysis reveals causal relationship between tonsillectomy and irritable bowel syndrome - Liu, Huaiquan; Shao, Shuoshuo; Chen, Bo; Yang, Shili; Zhang, Xinyan (Frontiers in Surgery, 2025)
ObjectiveThis study used two sample Mendelian randomization (MR) method to evaluate the causal relationship between tonsillectomy and irritable bowel syndrome (IBS).MethodsWe selected tonsillectomy as the exposure factor and IBS as the outcome variable, using GWAS data from the IEU Open GWAS project. Instrumental variables (IVs) were SNPs strongly correlated and independent of tonsillectomy. MR-PRESSO was used for outlier removal. IVW was the primary MR analysis method, supplemented by MR-Egger regression, WM, WME, and simple mode. Cochran's Q tests assessed heterogeneity. MR-Egger intercept tested horizontal pleiotropy. Sensitivity analysis used a leave-one-out method.ResultsThe IVW analysis indicated a positive association between genetically predicted tonsillectomy and IBS (OR = 1.682, 95% CI: 1.157–2.446, P = 0.006). Heterogeneity tests revealed the presence of heterogeneity at the SNPs (Cochran Q test, P = 3.13 × 10−5. The MR-Egger intercept test did not detect horizontal pleiotropy (egger_intercept = 0.000914, P = 0.789). Sensitivity analysis demonstrated the stability of the results. All F-statistics were greater than 10, indicating the absence of weak instrument bias.ConclusionGenetics predicts a positive causal relationship between tonsillectomy and IBS, suggesting that prevention of IBS in tonsillectomy patients should be enhanced.